Simplified bacterial denitrification method using Stenotrophomonas nitritireducens for nitrite dual isotope analysis in low-concentration environmental samples - Deb, Sushmita; Lewicka-Szczebak, Dominika (Frontiers in Environmental Science, 2025)
This study presents a simplified and optimized bacterial denitrification method using Stenotrophomonas nitritireducens for precise nitrite isotope analysis in low-concentration environmental samples. The improved method reduces the bacterial cultivation period from approximately 3–4 weeks to just 24 h. Additionally, it allows for reliable nitrite analyses at concentrations as low as 150 nmol NO2− L-1, enabling analyses at concentrations of approximately one order of magnitude lower compared to previous methods. Three treatments were tested to evaluate their impact on isotopic precision and accuracy: Treatment 1 used a direct incubation approach, Treatment 2 incorporated an additional growth step of re-inoculation of the bacterial culture into fresh medium, and Treatment 3 included a 24-h stabilization step at 4°C after the initial incubation. The method was validated using internal standards and applied to environmental samples, achieving good precision. Isotope ratio mass spectrometry (IRMS) measurements demonstrated superior accuracy for Treatment 1, with mean accuracies of ±0.7‰ for δ15N and ±0.4‰ for δ18O, while Treatment 2 (±2.0‰ for δ15N and ±1.7‰ for δ18O) and Treatment 3 (±1.8‰ for δ15N and ±4.3‰ for δ18O) showed lower precision. Among the treatments, Treatment 1 delivered the most accurate and reproducible results, showing minimal deviations of the measured N2O values from the true nitrite values. The oxygen isotope exchange between water and NO2− during bacterial conversion ranged from 7% to 16%, which is similar to previous methods. This study integrates advanced analytical tools, such as laser spectroscopy and isotope ratio mass spectrometry, enabling reliable isotopic measurements even at trace nitrite concentrations. IRMS offered higher precision for high concentrations, while laser spectroscopy was better suited for repeated measurements at trace levels in low-concentration samples. The enhancements in the cultivation efficiency, detection sensitivity, and precision make this approach highly valuable for environmental studies, especially in tracing nitrogen transformations in soil and water systems.